AI/Machine Learning for Internet of Dependable and Controllable Things - Song, Houbing (ACM, 2023)
The Internet of Things (IoT) has the potential to enable a variety of applications and services. However, it also presents grand challenges in security, safety, and privacy. Therefore, there is a need for moving from IoT to Internet of Dependable Things, which is defined as Internet of Things which is designed, built, deployed and operated in a highly trustworthy manner, and Internet of Controllable Things, which is defined as Internet of Things which is operated in a highly controllable manner. A massive resurgence of artificial intelligence (AI) and machine learning (ML) presents tremendous opportunities for Internet of Dependable and Controllable Things and as well as significant challenges to Internet of Dependable and Controllable Things. In this lecture, I will present the state of the art by reviewing and classifying the existing literature, evaluate the opportunities and challenges, and identify trends by evaluating what needs to be done to enable AI/Machine Learning for Internet of Dependable and Controllable Things.
MM '23: The 31st ACM International Conference on Multimedia; Ottawa, ON, Canada; 29 October 2023
Keywords: Artificial intelligence; Machine learning; Internet of Things